Vocational Education in Schools: A Tool to Overcome the Drop-Out Rate in Public Funded Institutions - Unnisa, Dr. Viquar (Voices of Teachers and Teacher Educators, 2020)
Access to quality education is the fundamental right in India and it is the foundation for sustainable development. Indian education system after independence has made great progress, and is now accessible to a large segment of the society. The government has set up various educational committees, right from Dr. Radhakrishnan committee 1948-49 to the proposed National Education Policy 2020 with an objective to address the challenges of education. AThese have recommended comprehensive steps to improve education system in India. The broad objective of all educational policies has beento address the questions of access, equityand quality apart from other issues as per the then existing needs.A special focus has almost always been also on the universalisation of School education and achievement of 100% Gross Enrollment Ratio(GER)at national and state level. The UDISE report says that “India has made remarkable strides in recent years in attaining near universal enrollment in Primary schools, according to U-DISE data GER in 2016-17 for grades 1-5 was 95.1%.The data indicates some serious issues in retaining children in the schooling system for later grades. For classes 6-8 GER is 90.7%, while for Grades 9-10 and 11-12 it was only 79.3% and 51.3% respectively”(U-DISE).Furthermore, the report indicates that a large proportion of students -drop out after 8th class. Policy makers have been concerned about how to retain these students in the educational fold. The present study has attempted to find what the dropped out students are doing after discontinuation of the studies and to suggest few strategies to prevent further students from dropping-out. The study was done in Hyderabad District, which is the capital of Telangana state. The data is collected from the parents or guardians of dropped out students who had been studying in government schools. Purposive sampling technique is adopted and the addresses of the students were taken from the schools located in the study area. It is concluded that the most of the families whose children are studying in Government schools, Hyderabad migrated from rural to urban areas in search of livelihood. Moreover, according to the U-DISE data for the year 2016-17 Telangana State witnessed almost a double dropout rate up-to class VIII during 2016-17 compared to previous year.